Preparation process of highly graphitized fuel cell microporous layer with hierarchical pore structure and gradient wetting performance
By adopting a highly graphitized microporous layer with graded pore structure and gradient wetting performance in fuel cells, the problem of insufficient water and gas management capabilities of PEMFC under different working conditions is solved, and excellent water within the entire humidity range is achieved. Improved gas management performance and overall performance.
Patent Information
- Application Number
- CN202411568599.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing proton exchange membrane fuel cell (PEMFC) is difficult to effectively manage water and gas under different operating conditions, resulting in performance losses, especially in the conditions of 0%-100% full humidity.
Using a highly graphitized fuel cell microporous layer preparation process with graded pore structure and gradient wetting properties, the preparation of homogeneous viscous spinning liquid, the preparation of graded pore structure fiber membrane, highly graphitized treatment and gradient wetting The step of proactive modification is to prepare a microporous layer that can maintain good water and gas management performance within the entire humidity range.
Good water and gas management performance of fuel cells under full humidity conditions of 0%-100%, reducing ohmic impedance and installation difficulty, and significantly improving the overall performance of fuel cells.
Smart Images

Figure CN119419288A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of proton exchange membrane fuel cells, and in particular relates to a process for preparing a highly graphitized fuel cell microporous layer with a graded pore structure and gradient wetting properties. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) have become an ideal choice for global sustainable development strategies due to their high energy conversion efficiency, fast startup speed, and low emissions. However, due to the existence of activation polarization, ohmic polarization, and concentration polarization, PEMFCs suffer overall performance losses during operation.
[0003] To improve the overall performance of PEMFC, researchers have focused on reducing polarization losses under different operating conditions. Initially, gas diffusion layers consisted only of carbon paper or carbon cloth, which provided elemental gas diffusion and structural support. However, these early designs suffered from insufficient water and gas management performance, limiting the scalability and wider application of PEMFC. In the early 1990s, researchers at Ballard Power Systems made a breakthrough by coating one side of the gas diffusion layer (hereinafter referred to as GDL) closest to the catalyst layer with microporous carbon materials. This innovative design significantly enhances water and gas management performance, thereby improving the overall performance of the fuel cell and becoming a key component of PEMFC design. Since then, the microporous layer (hereinafter referred to as MPL) has been the focus of extensive research, and various materials and structures have been developed to optimize mass transfer, reduce polarization losses, and improve the efficiency and durability of PEMFC.
[0004] At present, the design of MPL is mainly divided into hydrophilic type, hydrophobic type and hydrophilic-hydrophobic composite type. For example, Wuxi Weifu High-Tech Group Co., Ltd. discloses a hydrophilic microporous layer of a proton exchange membrane fuel cell membrane electrode and a preparation method (CN118738429A). Specifically, a hydrophilic microporous layer slurry is prepared by mixing a carbon material and a hydrophilic polymer, and then coated on the microporous layer of a cathode catalyst layer or a cathode gas diffusion layer. After drying, a hydrophilic microporous layer of a proton exchange membrane fuel cell membrane electrode is obtained, which improves the performance of PEMFC at a relative humidity of 20% to 50%.
[0005] Shanghai Electric Group Co., Ltd. discloses a gas diffusion layer and its preparation method, membrane electrode and fuel cell (CN118367157A). Specifically, carbon, a hydrophobic agent and a dispersant are placed on a carbon paper substrate, and then calcined after standing for a period of time at a specific temperature to obtain a hydrophobic microporous layer, thereby improving the drainage performance of the fuel cell.
[0006] Dalian Meiniu New Energy Co., Ltd. discloses a gas diffusion layer gradient pore structure and its construction method and application (CN118299591A). Specifically, conductive carbon powder material is made into slurry with polystyrene microspheres of different particle sizes, and then coated on the surface of carbon paper according to the particle size from small to large. Finally, the coated hydrophobic carbon paper is subjected to high-temperature heat treatment to form a pore structure of different sizes and gradient changes, which can effectively improve the gas and liquid transmission performance of the gas diffusion layer.
[0007] China Automotive Innovation Technology Co., Ltd. has disclosed a gas diffusion layer and its preparation method and application (CN118841578A). Specifically, a hydrophilic reagent mainly composed of sodium dioctyl sulfonate, ethyl acetate and / or polyethylene glycol and water is sprayed on a hydrophobic microporous layer by an atomization process and calcined, thereby preparing a microporous layer with hydrophilic and hydrophobic composite properties, thereby achieving improved membrane electrode performance under high current density conditions.
[0008] Their similarities are: they all improve the water and gas management performance of PEMFC under a small relative humidity range by wettability modification and structural design of MPL; their differences are: a gas diffusion layer and its preparation method, membrane electrode and fuel cell (CN118367157A) is a single-layer MPL with only hydrophobic properties; while a proton exchange membrane fuel cell membrane electrode hydrophilic microporous layer and preparation method (CN118738429A), a gas diffusion layer gradient pore structure and its construction method and application (CN118299591A), a gas Diffusion layer and its preparation method and application (CN118841578A) are all multilayer MPL, among which a gas diffusion layer gradient pore structure and its construction method and application (CN118299591A) constructs a gradient pore structure in the vertical direction, a proton exchange membrane fuel cell membrane electrode hydrophilic microporous layer and preparation method (CN118738429A) and a gas diffusion layer and its preparation method and application (CN118841578A) prepare a microporous layer with both hydrophilic and hydrophobic composite properties through a multilayer composite structure. The single-layer MPL with gradient pore structure and wetting properties that adapts to 0%-100% full humidity working conditions is not involved. Summary of the invention
[0009] In view of the different requirements of fuel cells for efficient water and gas management under different operating conditions, the purpose of the present invention is to provide a process for preparing a highly graphitized fuel cell microporous layer with a graded pore structure and gradient wetting properties, so that the prepared microporous layer can have good water and gas management capabilities under 0%-100% full humidity operating conditions, thereby significantly improving the performance of the fuel cell.
[0010] 1. A process for preparing a highly graphitized fuel cell microporous layer with a hierarchical pore structure and gradient wettability, characterized in that it comprises the following steps:
[0011] Step 1: preparing a homogeneous viscous spinning solution, uniformly dispersing carbon black particles and polyvinyl pyrrolidone (hereinafter referred to as PVP) in an ethanol solution to prepare a homogeneous spinning solution with a specific viscosity;
[0012] Step 2: Preparation of fiber membrane with hierarchical pore structure: electrospinning the homogeneous viscous spinning solution under specific spinning parameters, removing the fiber membrane after spinning and applying specific pressure to prepare a fiber membrane with hierarchical pore structure;
[0013] Step 3: Highly graphitized, after the fiber membrane is dried at a specific temperature, carbon paper is used as a fixture to hold the fiber membrane for stabilization and pre-oxidation at a specific temperature to control uniform shrinkage; the uniformly shrunk fiber membrane is clamped with a high-purity graphite plate as a fixture, and under specific temperature and atmosphere conditions, the fiber membrane is controlled to shrink uniformly again and induce graphitization;
[0014] Step 4: Gradient wettability modification, immersing the graphitized fiber membrane in a certain concentration of polytetrafluoroethylene (hereinafter referred to as PTFE) dispersion, controlling the wettability by controlling the concentration of the dispersion and the immersion time, drying it after immersion to remove moisture, and then melting and hot pressing the PTFE at a specific temperature for a certain period of time, so that the PTFE and the graphitized fiber membrane are consolidated together, and the PTFE is gradiently distributed in the vertical direction of the fiber membrane, thereby constructing gradient wettability.
[0015] 2. The preparation of the homogeneous viscous spinning solution in step 1 is characterized by:
[0016] The molecular weight of PVP is 1,000,000 to 1,500,000, and the mass fraction is 6% to 12%; the carbon black particles are one or more of 0-dimensional carbon materials such as acetylene black, pigment carbon black, or Ketjen carbon black, and the mass fraction is 12% to 18% of the total mass of PVP and carbon black;
[0017] The key to the homogeneous spinning solution preparation process is to slowly add acetylene black to the ethanol solution at a magnetic stirrer speed of 800rppm to 1000rppm, then perform ice bath ultrasound for 40 to 60 minutes, then add PVP and stir for 4 to 6 hours.
[0018] 3. The preparation of the hierarchical pore structure fiber membrane in step 2 is characterized by:
[0019] The electrospinning process is adopted, the positive and negative voltages of the spinning are +8~+10kV and -7~-9kV respectively, the receiving screen is a metal roller with silicone oil paper attached, the distance between the receiving roller and the spinning needle is 9~11cm, the roller speed is 300~400rppm, the inner diameter of the spinning needle is 0.4~0.6mm, and the solution advancement speed is 1.5~2.2mL / h;
[0020] Under the action of electrostatic force, the fiber membrane forms a hierarchical pore structure with small pores, mesopores and macropores on the horizontal plane;
[0021] The spinning solution is the homogeneous viscous spinning solution prepared in step 1 in which carbon black particles are dispersed. During the spinning process, due to the local aggregation of carbon black particles at a microscopic scale, fibers are bonded to each other, the contact area is increased, and the ohmic impedance in the vertical direction is reduced;
[0022] After the electrospinning is completed and before the ethanol is completely volatilized, the specific pressure applied to the fiber membrane is 1.5-2.0 N / cm 2 , making the fiber membrane overlap more closely in the vertical direction, further reducing the ohmic impedance.
[0023] 4. In step 3, the high degree of graphitization is characterized by:
[0024] The fiber membrane is dried at a temperature of 50-60°C for 3-4 hours in an air atmosphere to completely volatilize the ethanol;
[0025] The stabilization process is characterized in that the fiber membrane is removed from the silicone oil paper, the fiber membrane is cut to a specific size, the fiber membrane is clamped in the center of the carbon paper using carbon paper as a clamp, and the four corners of the carbon paper are clamped with paper clips, so that the external air is uniformly in contact with the fiber membrane through the carbon paper, and the fiber membrane is controlled to shrink uniformly; the stabilization temperature is 140-160° C., the air atmosphere, the heating and cooling rates are both 1° C. / min, and the insulation time is 12-20 hours, so that the PVP is dehydrogenated and cyclized, and is converted from a thermoplastic polymer to a thermosetting polymer, so as to prevent the PVP from melting in the subsequent heat treatment process and thus destroying the fiber morphology;
[0026] The pre-oxidation process is characterized in that it is still carried out under the carbon paper sandwich, so that the fiber membrane is evenly exposed to oxygen in the external air to prevent curling and non-uniform shrinkage, the temperature is 350-370°C, the air atmosphere, the heating rate and the cooling rate are both 2°C / min, the insulation time is 4-5h, so that the side chains of the PVP molecules are destroyed, the main chains of the PVP molecules are oxidized and the fibers are thinned;
[0027] The carbonization process is characterized in that the pre-oxidized fiber membrane is taken out from the carbon paper, and a high-purity graphite plate with a thickness of 1 mm is used as a clamp to clamp the fiber membrane to induce graphitization of the fiber membrane. The carbonization temperature is 1100-1300°C, the nitrogen or argon atmosphere, the heating and cooling rates are 3-5°C / min, and the insulation time is 4-5h, so that the fiber is refined, the PVP is completely dehydrogenated and converted into an amorphous state, a chaotic layer graphite structure is formed, and the conductivity of the nanofiber is increased. Since the carbon black particles do not have shrinkage properties, non-homogeneous shrinkage occurs at the microscopic scale, and the fiber surface presents corrugations and a large number of grooves, while at the macroscopic scale, a relatively flat horizontal surface is presented due to the effect of the graphite sheets.
[0028] 5. The gradient wettability modification in step 4 is characterized by:
[0029] The mass fraction of PTFE in the PTFE dispersion is 10%, the dispersant is distilled water, the immersion time is 30-40 minutes, the drying temperature is 60-70°C, and the insulation time is 6-10 hours, so that the water evaporates completely. During the drying process, the fiber membrane is kept horizontally so that the PTFE is evenly distributed on the horizontal plane;
[0030] The melting temperature is 340-360°C, the heating rate is 2°C / min, and the insulation time is 2-5h. During the melting process, high-purity graphite plates are still used as fixtures. At the same time, the fixtures provide a certain pressure on the fiber membranes between the graphite plates, and the fiber membranes are kept horizontally, so that the PTFE melt forms a uniform gradient deposition in the vertical direction due to gravity and pressure, and adheres to the corrugated surface and grooves of the fiber in step 3 without affecting the overall electron transmission performance. When used in a fuel cell, it can effectively avoid the loss of PTFE and the performance degradation of the battery water pipe.
[0031] Beneficial effects of the present invention: the hierarchical pore structure of micropores, mesopores and macropores on the planar structure of the microporous layer prepared by the above steps ensures good water and gas transmission channels; the gradient PTFE content distribution in the vertical direction constructs gradient wetting performance, effectively avoiding proton membrane dehydration under low humidity and catalyst layer flooding under high humidity, and achieving good water and gas management performance under full humidity conditions (0% to 100% relative humidity); the entangled fibers and the induced highly graphitized structure provide good electron transmission channels; on the whole, not only the excellent water and gas management performance of the fuel cell under full humidity is guaranteed, but also the ohmic impedance and installation difficulty are effectively reduced, thereby improving the overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A process flow for preparing a highly graphitized fuel cell microporous layer with hierarchical pore structure and gradient wettability
[0033] Figure 2 SEM image of the hierarchical pore structure of the prepared microporous layer
[0034] Figure 3 SEM image of the vertical cross-section of the prepared microporous layer with highly layered graphitized structure
[0035] Figure 4 SEM image of fiber entanglement structure on the vertical surface of the prepared microporous layer
[0036] Figure 5 EDS image of the F element distribution on the vertical section of the prepared microporous layer
[0037] Figure 6 EDS image of the gradient distribution of F element on the vertical section of the prepared microporous layer DETAILED DESCRIPTION
[0038] Embodiment 1:
[0039] 1.2 g of acetylene black was slowly added to 69 g of stirring ethanol, and after ice bath ultrasonication for 1 h, 6 g of polyvinyl pyrrolidone (PVP) with a molecular weight of 1,300,000 was slowly added, and stirred at 900 rppm for 5 h to obtain a homogeneous viscous spinning solution.
[0040] Take 18mL of the spinning solution prepared in the above steps for electrospinning, the spinning needle is No. 21, the spinning distance is 10.5cm, the spinning voltage is +9.5kV and -8.5kV, the propulsion speed is 2.0mL / min, the receiving roller speed is 300rppm, the roller length is 20cm, and the roller diameter is 30cm. A fiber membrane with a hierarchical pore structure with a thickness of 180μm is obtained. Before the ethanol is completely evaporated, a glass plate is used to clamp the fiber membrane and apply 1.75N / cm 2 The glass plate was then removed and placed in an oven at 55°C for 4 h to allow the solvent to evaporate completely.
[0041] Take the above fiber membrane and cut it into 10cm×10cm fiber membrane, sandwich it between two pieces of TGP-H-060 model carbon paper (10cm×10cm) produced by Toray, and place it in a muffle furnace. The heating rate is 1℃ / min. After keeping it at 150℃ for 15h, it is heated to 360℃ at a heating rate of 2℃ / min and kept for 4h. It is cooled to room temperature at a cooling rate of 2℃ / min to obtain a fiber membrane with a size of about 5cm×5cm and a thickness of about 140μm; it is sandwiched in a high-purity graphite plate, placed in a muffle furnace, and kept at 1100℃ for 4h under argon atmosphere. The heating rate and cooling rate are both 5℃ / min to obtain a highly graphitized fiber membrane with a thickness of about 120μm and a length and width of 4cm×4cm.
[0042] Take the above-mentioned graphitized fiber membrane, place it in a 10% PTFE suspension (the solvent is water) and soak it for 30 minutes. After taking it out, place it horizontally on a graphite plate and keep it in a 60°C oven for 10 hours. After the water is completely evaporated, it is clamped in a graphite plate and placed horizontally in a muffle furnace at 350°C for 2 hours. The heating rate and cooling rate are both 2°C / min. Under the action of gravity and clamp pressure, the molten PTFE is distributed in a gradient shape in the grooves formed by shrinkage during the fiber graphitization process, and finally a highly graphitized fuel cell microporous layer with a graded pore structure and gradient wetting properties is obtained.
[0043] The microporous layer was installed on the cathode side of a 2 cm × 2 cm fuel cell (anode: YLS35T, CCM: Nafion211 & 0.12 / 0.24 mg.cm -2 Pt, cathode MPS: TGP-H-060@40%PTFE), under the conditions of H2 flow rate of 0.2L / min, O2 flow rate of 0.7L / min, and stack temperature of 80℃, 1.80A.cm were obtained under the conditions of 0%, 20%, 40%, 60%, and 100% relative humidity. -2 、1.86A.cm -2 , 2.05A.cm -2 、2.09A.cm -2 、1.45A.cm -2 、1.36A.cm -2 The power density of the GDL is 1.5A.cm2 at 0%, 20%, 40%, 60%, and 100% relative humidity respectively. -2 、1.3A.cm -2 、0.8A.cm -2 、0.6A.cm -2 (100% RH flooding is serious). The prepared highly graphitized fuel cell microporous layer with graded pore structure and gradient wettability can effectively improve the overall performance of the fuel cell.
[0044] Embodiment 2:
[0045] 1.0 g of pigment carbon black was slowly added to 69 g of stirring ethanol, and after ice bath ultrasonication for 50 min, 6 g of polyvinyl pyrrolidone (PVP) with a molecular weight of 1,300,000 was slowly added, and stirred at 900 rppm for 6 h to obtain a homogeneous viscous spinning solution.
[0046] Take 16mL of the spinning solution prepared in the above steps for electrospinning, the spinning needle is No. 21, the spinning distance is 11cm, the spinning voltage is +10.0kV and -9.0kV, the propulsion speed is 2.2mL / min, the receiving roller speed is 300rppm, the roller length is 20cm, and the roller diameter is 30cm. A fiber membrane with a thickness of 160μm and a hierarchical pore structure is obtained. The fiber membrane is sandwiched by a glass plate and applied with 1.80N / cm 2 The glass plate was then removed and placed in an oven at 60°C for 4 h to allow the solvent to evaporate completely.
[0047] Take the above fiber membrane and cut it into 10cm×10cm fiber membrane, sandwich it between two pieces of TGP-H-060 model carbon paper (10cm×10cm) produced by Toray, and place it in a muffle furnace. The heating rate is 1℃ / min. After keeping it at 140℃ for 12h, it is heated to 360℃ at a heating rate of 2℃ / min and kept for 4h. It is cooled to room temperature at a cooling rate of 2℃ / min to obtain a fiber membrane with a size of about 5cm×5cm and a thickness of about 120μm; it is sandwiched in a high-purity graphite plate, placed in a muffle furnace, and kept at 1300℃ for 4h under a nitrogen atmosphere. The heating rate and cooling rate are both 5℃ / min to obtain a highly graphitized fiber membrane with a thickness of about 100μm and a size of about 4cm×4cm.
[0048] Take the above-mentioned graphitized fiber membrane, place it in a 10% PTFE suspension (the solvent is water) and soak it for 40 minutes. After taking it out, place it horizontally on a graphite plate and keep it in a 70°C oven for 6 hours. After the water is completely evaporated, it is clamped in a graphite plate and placed horizontally in a muffle furnace at 350°C for 2 hours. The heating rate and cooling rate are both 2°C / min. Under the action of gravity and clamp pressure, the molten PTFE is distributed in a gradient shape in the grooves formed by shrinkage during the fiber graphitization process, and finally a highly graphitized fuel cell microporous layer with a graded pore structure and gradient wetting properties is obtained.
[0049] The microporous layer was installed on the cathode side of a 2 cm × 2 cm fuel cell (anode: YLS30T, CCM: Nafion211 & 0.12 / 0.24 mg.cm -2 Pt, cathode MPS: TGP-H-060@40%PTFE), under the conditions of H2 flow rate of 0.22L / min, O2 flow rate of 0.8L / min, and stack temperature of 80℃, 1.87A.cm were obtained under the conditions of 0%, 20%, 40%, 60%, and 100% relative humidity. -2 、1.94A.cm -2 、2.18A.cm -2 , 2.22A.cm -2 , 2.20A.cm-2 , 2.05A.cm -2 power density.
[0050] Matters not covered by the present invention are known technologies.
[0051] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing a highly graphitized fuel cell microporous layer with a hierarchical pore structure and gradient wettability, characterized in that: The steps include: Step 1: preparing a homogeneous viscous spinning solution, uniformly dispersing carbon black particles and polyvinyl pyrrolidone (hereinafter referred to as PVP) in an ethanol solution to prepare a homogeneous spinning solution with a specific viscosity; Step 2: Preparation of fiber membrane with hierarchical pore structure: electrospinning the homogeneous viscous spinning solution under specific spinning parameters, removing the fiber membrane after spinning and applying specific pressure to prepare a fiber membrane with hierarchical pore structure; Step 3: Highly graphitized, after the fiber membrane is dried at a specific temperature, carbon paper is used as a fixture to hold the fiber membrane for stabilization and pre-oxidation at a specific temperature to control uniform shrinkage; the uniformly shrunk fiber membrane is clamped with a high-purity graphite plate as a fixture, and under specific temperature and atmosphere conditions, the fiber membrane is controlled to shrink uniformly again and induce graphitization; Step 4: Gradient wettability modification, immersing the graphitized fiber membrane in a certain concentration of polytetrafluoroethylene (hereinafter referred to as PTFE) dispersion, controlling the wettability by controlling the concentration of the dispersion and the immersion time, drying it after immersion to remove moisture, and then melting and hot pressing the PTFE at a specific temperature for a certain period of time, so that the PTFE and the graphitized fiber membrane are consolidated together, and the PTFE is gradiently distributed in the vertical direction of the fiber membrane, thereby constructing gradient wettability.
2. The preparation of the homogeneous viscous spinning solution in step 1 is characterized by: The molecular weight of PVP is 1,000,000 to 1,500,000, and the mass fraction is 6% to 12%; the carbon black particles are one or more of 0-dimensional carbon materials such as acetylene black, pigment carbon black, or Ketjen carbon black, and the mass fraction is 12% to 18% of the total mass of PVP and carbon black; The key to the homogeneous spinning solution preparation process is to slowly add acetylene black to the ethanol solution at a magnetic stirrer speed of 800rppm to 1000rppm, then perform ice bath ultrasound for 40 to 60 minutes, then add PVP and stir for 4 to 6 hours.
3. The preparation of the hierarchical pore structure fiber membrane in step 2 is characterized by: The electrospinning process is adopted, the positive and negative voltages of the spinning are +8~+10kV and -7~-9kV respectively, the receiving screen is a metal roller with silicone oil paper attached, the distance between the receiving roller and the spinning needle is 9~11cm, the roller speed is 300~400rppm, the inner diameter of the spinning needle is 0.4~0.6mm, and the solution advancement speed is 1.5~2.2mL / h; Under the action of electrostatic force, the fiber membrane forms a hierarchical pore structure with small pores, mesopores and macropores on the horizontal plane; The spinning solution is the homogeneous viscous spinning solution prepared in step 1 in which carbon black particles are dispersed. During the spinning process, due to the local aggregation of carbon black particles at a microscopic scale, fibers are bonded to each other, the contact area is increased, and the ohmic impedance in the vertical direction is reduced; After the electrospinning is completed and before the ethanol is completely volatilized, the specific pressure applied to the fiber membrane is 1.5-2.0 N / cm 2 , making the fiber membrane overlap more closely in the vertical direction, further reducing the ohmic impedance.
4. In step 3, the high degree of graphitization is characterized by: The fiber membrane is dried at a temperature of 50-60°C for 3-4 hours in an air atmosphere to completely volatilize the ethanol; The stabilization process is characterized in that the fiber membrane is removed from the silicone oil paper, the fiber membrane is cut to a specific size, the fiber membrane is clamped in the center of the carbon paper using carbon paper as a clamp, and the four corners of the carbon paper are clamped with paper clips, so that the external air is uniformly in contact with the fiber membrane through the carbon paper, and the fiber membrane is controlled to shrink uniformly; the stabilization temperature is 140-160° C., the air atmosphere, the heating and cooling rates are both 1° C. / min, and the insulation time is 12-20 hours, so that the PVP is dehydrogenated and cyclized, and is converted from a thermoplastic polymer to a thermosetting polymer, so as to prevent the PVP from melting in the subsequent heat treatment process and thus destroying the fiber morphology; The pre-oxidation process is characterized in that it is still carried out under the carbon paper sandwich, so that the fiber membrane is evenly exposed to oxygen in the external air to prevent curling and non-uniform shrinkage, the temperature is 350-370°C, the air atmosphere, the heating rate and the cooling rate are both 2°C / min, the insulation time is 4-5h, so that the side chains of the PVP molecules are destroyed, the main chains of the PVP molecules are oxidized and the fibers are thinned; The carbonization process is characterized in that the pre-oxidized fiber membrane is taken out from the carbon paper, and a high-purity graphite plate with a thickness of 1 mm is used as a clamp to clamp the fiber membrane to induce graphitization of the fiber membrane. The carbonization temperature is 1100-1300°C, the nitrogen or argon atmosphere, the heating and cooling rates are 3-5°C / min, and the insulation time is 4-5h, so that the fiber is refined, the PVP is completely dehydrogenated and converted into an amorphous state, a chaotic layer graphite structure is formed, and the conductivity of the nanofiber is increased. Since the carbon black particles do not have shrinkage properties, non-homogeneous shrinkage occurs at the microscopic scale, and the fiber surface presents corrugations and a large number of grooves, while at the macroscopic scale, a relatively flat horizontal surface is presented due to the effect of the graphite sheets.
5. The gradient wettability modification in step 4 is characterized by: The mass fraction of PTFE in the PTFE dispersion is 10%, the dispersant is distilled water, the immersion time is 30-40 minutes, the drying temperature is 60-70°C, and the insulation time is 6-10 hours, so that the water evaporates completely. During the drying process, the fiber membrane is kept horizontally so that the PTFE is evenly distributed on the horizontal plane; The melting temperature is 340-360°C, the heating rate is 2°C / min, and the insulation time is 2-5h. During the melting process, high-purity graphite plates are still used as fixtures. At the same time, the fixtures provide a certain pressure on the fiber membranes between the graphite plates, and the fiber membranes are kept horizontally, so that the PTFE melt forms a uniform gradient deposition in the vertical direction due to gravity and pressure, and adheres to the corrugated surface and grooves of the fiber in step 3 without affecting the overall electron transmission performance. When used in a fuel cell, it can effectively avoid the loss of PTFE and the performance degradation of the battery water pipe.
Citation Information
Patent Citations
Gas diffusion layer gradient hole structure and construction method and application thereof
CN118299591A
Gas diffusion layer and preparation method thereof, membrane electrode and fuel cell
CN118367157A
Membrane electrode hydrophilic microporous layer of proton exchange membrane fuel cell and preparation method of membrane electrode hydrophilic microporous layer
CN118738429A
Gas diffusion layer and preparation method and application thereof
CN118841578A
Electrode material with fiber structure and preparation and application thereof
CN112952121A
Cited By
Carbon fiber paper with gradient pore structure as well as preparation method and preparation device of carbon fiber paper
CN119640611A
Microporous layer with humidity self-adjusting function and preparation method thereof
CN120319822A